دراسة الخصائص التغذوية والميكروبية لبعض الفطائر المصنعة في المنطقة الساحلية - حرفوش, محسن (Latakia University Journal -Biological Sciences Series, 2014)
يهدف هذا البحث إلى دراسة التركيب الكيميائي والحمولة الميكروبية لبعض أنواع الفطائر باستخدام العديد من التحاليل الكيميائية والميكروبية لعينات جمعت من مناطق مختلفة من الساحل السوري. أوضحت هذه الدراسة التباين الكبير في التركيب الكيميائي للعينات حسب نوع الفطيرة والمكان الذي جمعت منه. كانت نسبة المادة الجافة لفطائر الفليفلة والسلق التي جمعت من بانياس 75.71% و 44.90% على التوالي وكانت نسبة المادة الجافة 73.88% و76.18% ونسبة البروتين 17.76% و24.88% لفطائر الجبن التي جمعت من طرطوس واللاذقية 1 على التوالي, كما بينت هذه الدراسة أن جميع الفطائر تحتوي نسبة عالية من الدهن وكانت أقل نسبة في فطائر السلق (17.64%) وأعلى نسبة في فطائر الجبنة (38.12%) ونسبة عالية من الصوديوم حيث كانت أعلاها في فطائر الجبنة (15.31 ملغ/100غ) وأقلها في فطائر الفليفلة (7.82 ملغ/100غ)، كذلك أظهرت الدراسة أن هذه الوجبات مطابقة للمعايير العالمية من حيث المحتوى من الكادميوم والرصاص وفقيرة بالألياف باستثناء فطائر السلق التي كانت أكثرها توازناً من حيث المكونات مما يجعلها أفضل أنواع الفطائر من ناحية الألياف الغذائية. أخيراً, أوضحت النتائج أن الحمولة الميكروبية مرتفعة جداً حيث كان التعداد الكلي للجراثيم أعلى من 105 والتعداد الكلي للخمائر والفطور أعلى من 102 وكانت جميع الفطائر مخالفة للمواصفة القياسية السورية، كما بينت النتائج غياب E. coli و St. aureus من جميع العينات. The objective of this research to study the chemical composition and microbial load for some types of pies by performing various chemical and microbial analysis of samples collected, from different parts of the Syrian coast which are famous for its production. This study showed a large variation in the chemical composition of samples by type of the pastry and place brought from, for example, the proportion of dry matter for peppers and chard pies collected from Banias was, 75.71% and 44.90%, respectively, and the percentage of dry matter was 73.88% and 76.18% and the proportion of protein was, 17.76% and 24 .88% for cheese pies collected from Tartous and Latakia 1, respectively. This study indicated that all the pies contain a high percentage of fat [the lowest in chard pies (17.64%) and the highest in cheese pies (38.12%)]. Furthermore a high percentage of sodium was found (the highest in cheese pies 15.31 mg / 100 g and lowest in pepper pies 7.82 mg / 100 g). The study also showed that these meals meet international standards in terms of content of lead, cadmium, Nevertheless they are poor in fiber content except for chard pies which were the most balanced in terms of components, making it the best type of pies in nutritional aspect. Finally, the results showed that the microbial load was too high, as the total census of bacteria was higher than 105 and the total census of yeasts and fungi was higher than 102. In addition, all pies are not conformed to the Syrian legislation. The study also showed absence of E.coli and St. aureus of all samples.